Estimation of Viscoelastic Properties of Cells Using Acoustic Tweezing Cytometry. (25th October 2016) - Yang, Chunmei; Chen, Di; Hong, Xiaowei
Abstract : Objectives: Recently developed acoustic tweezing cytometry uses ultrasound‐responsive targeted microbubbles for biomechanical stimulation of live cells at the subcellular level. The purpose of this research was to estimate the viscoelastic characteristics of cells from the displacements of cell‐bound microbubbles in response to ultrasound pulses on acoustic tweezing cytometry. Methods: Microbubbles were bound to NIH/3T3 fibroblasts and ATDC5 cells through an integrin‐cytoskeleton linkage. The evolution of microbubble behaviors under irradiation by ultrasound pulses was captured by a high‐speed camera and tracked by a customized algorithm. The total damping constant, stiffness, and rigidity of the cells were estimated by fitting the measured temporal displacement profiles to a Kelvin‐Voigt–based model. Results: The mean maximum displacement of the microbubbles attached to NIH/3T3 fibroblasts was much greater than that for ATDC5 cells. The mean fitted damping constant and stiffness ± SD for ATDC5 cells were 28.16 ± 7.08 mg/s and 0.5041 ± 0.1381 mN/m, respectively, and the values for NIH/3T3 fibroblasts were 13.12 ± 4.23 mg/s and 0.2591 ± 0.0715 mN/m. The rigidity for ATDC5 cells was 331.46 ± 106.50 MPa, whereas that for NIH/3T3 fibroblasts was 117.92 ± 34.83 MPa. Conclusions: The Arg‐Gly‐Asp‐integrin‐cytoskeleton system of NIH/3T3 fibroblasts appears to be softer than that of ATDC5 cells. The rigidity of ATDC5 cells was significantly greater than that of NIH/3T3 fibroblasts at the 95% confidence level. This strategy provides a novel way to determine the viscoelastic properties of the live cells.